Robotic-assisted versus open simple prostatectomy: Results from a systematic review and meta-analysis of comparative studies - Simone Scarcella (Korean Urological Association, 2021)
Purpose: To review safety and efficacy of robotic-assisted simple prostatectomy (RASP) compared to open simple prostatectomy (OP). Materials and Methods: A comprehensive literature search was performed to assess the differences in perioperative course and functional outcomes in patients with benign prostatic hyperplasia and surgical indication. The incidences of complications were pooled using the Cochran–Mantel–Haenszel Method and expressed as odds ratio (OR), 95% confidence interval (CI), and p-values. Perioperative course and functional outcomes were pooled using the inverse variance of the mean difference (MD), 95% CI, and p-values. Analyses were two-tailed and the significance was set at p<0.05. Results: Eight studies were accepted. Meta-analysis showed significantly longer surgical time (MD, 43.72; 95% CI, 30.57–56.88; p<0.00001) with a significantly lower estimated blood loss (MD, -563.20; 95% CI, −739.95 to −386.46; p<0.00001) and shorter postoperative stay (MD, −2.85; 95% CI, −3.72 to −1.99; p<0.00001) in RASP. Catheterization time did not differ (MD, 0.65; 95% CI, −2.17 to 3.48; p=0.65). The risk of blood transfusion was significantly higher in OP (OR, 0.23; 95% CI, 0.17–0.33; p<0.00001). The risk of recatheterization (OR, 1.96; 95% CI, 0.32–11.93; p=0.47), postoperative urinary infections (OR, 0.89; 95% CI, 0.23–3.51; p=0.87) and 30-day readmission rate (OR, 0.96; 95% CI, 0.61–1.51; p=0.86) did not differ. At 3-month follow-up, functional outcomes were similar. Conclusions: RASP demonstrated a better perioperative outcome and equal early functional outcomes as compared to OP. These findings should be balanced against the longer operative time and higher cost of robotic surgery.